2018
DOI: 10.3390/nano8120981
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Water-Based Nano-Perfumes

Abstract: The application of nanoemulsions as a novel delivery system for lipophilic materials, such as essential oils, flavors, and fragrances is one of the growing technologies used in cosmetic, pharmaceutical, and food industries. Their characteristic properties, like small droplet size with high interfacial area, transparent or semi-transparent appearance, low viscosity, and high kinetic stability, make them a perfect vehicle for fragrances, in the perfume industry. They could be a great alternative to water-based p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Its spherical nanodroplets are built of the non-polar tails of the surfactant molecules, which are directed to the micelle hydrophobic core formed by the oil phase. The polar heads of the surfactants are facing towards aqueous external phase [ 9 , 10 , 11 ]. Different oil and surfactant types which form the nanoemulsion droplets can influence the drug solubilization as a consequence of the difference in density, viscosity, and polarity.…”
Section: Introductionmentioning
confidence: 99%
“…Its spherical nanodroplets are built of the non-polar tails of the surfactant molecules, which are directed to the micelle hydrophobic core formed by the oil phase. The polar heads of the surfactants are facing towards aqueous external phase [ 9 , 10 , 11 ]. Different oil and surfactant types which form the nanoemulsion droplets can influence the drug solubilization as a consequence of the difference in density, viscosity, and polarity.…”
Section: Introductionmentioning
confidence: 99%
“…An American Addiction Centers are being available twenty four hours for any one need or explanation. Miastkowska et al (2018) advised water-based alcohol free perfumes for its safety, as the ethanol base perfumes obtainable on market may lead to skin irritation and inflammation besides poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with Tween, Cremophor EL possesses a stronger emulsifying capacity because of its larger amount of ethylene oxide, and Cremophor EL is more compatible with the oil phase [23]. In addition, the hydrophilic groups (polyethylene glycols and ethoxylated glycerol) of Cremophor EL could be incorporated with the aqueous phase, and the viscosity diversity between the oil-water interface was minimized, which caused a reduction in the critical Weber number and an increment of the droplet break-up efficiency [24]. Another study concluded that the PP of Cremophor is closer to the intermediate value than Tween, because the intermediate PP is crucial for the emulsifier to form fine oil droplets and transparent nanoemulsions [20].…”
Section: Dispersibility and Transmittance (%) Of The Snedds Compositionmentioning
confidence: 99%